Spatial coherence measurement of a high average power table-top soft X-ray laser - Attwood, D. T., author; Rocca, Jorge J., author; Chang, C., author; Tomasel, F. G., author; Seminario, M., author; Lui, Yanwei, author; EDP Sciences, publisher (Colorado State University. Libraries, 2001)
An extraordinarily high degree of spatial coherence from a high average power tabletop 46.9 nm laser was observed in two-pinhole interference experiments. Refractive anti-guiding and gain guiding along a capillary discharge-produced plasma column causes a rapid increase of the spatial coherence with amplifier length. Full spatial coherence was approached with a 36 cm long plasma of very high axial uniformity and a length to diameter ratio exceeding 1000: 1.